Medical knowledge, practices, and healing spaces in Córdoba del Tucumán, in the south of the Viceroyalty of Peru, 1573-1650 (2021)
The aim of this article is to study part of the effects of the process of the circulation of medical knowledge in the jurisdiction of Córdoba–governorate of Tucumán– at the end of the 16th century and the beginning of the 17th century. To do this, an investigation was conducted into the material environments of medical practices and the group of officials who acted within the framework of said environments, through a microanalysis anchored in unpublished documents from the Justice Fund of the Historical Archive of the Province of Córdoba and in the editions of the Acts of the City Council. It is argued that in the distinguishable healing spaces in the jurisdiction of Córdoba in the period mentioned, a repository of knowledge was created in which the humoral aetiology linked knowledge of an erudite origin with that which was part of the know-how of each officer, acquired through direct practice.